How do you think about stress? A qualitative analysis of beliefs about stress. (December 2021) - Kilby, Christopher Jon; Sherman, Kerry A; Wuthrich, Viviana
This qualitative study aimed to identify common stress beliefs. Undergraduate psychology students ( N = 35) completed semi-structured interviews discussing the sensations, causes, purpose, valence, consequences, control, and timeline of stress. Interviews were analysed via double-coded thematic analysis employing a latent, inductive, and realist framework. Five themes (cognition, emotion, physical health, interpersonal relations, and behaviour) and 17 subthemes were identified. Themes and subthemes were validated in a Delphi study of experts in stress research ( N = 14). Many of these identified beliefs have not been incorporated into current measures of stress beliefs, suggesting the need for new approaches to measuring this construct.